Possibility of Reducing the Thermal Conductivity of Ceramic Refractory Materials - A. W. Watan (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The research work covers a study of the possibility of producing porous ceramic bodies as a thermal insulators by adding fired Dechla kaolinite (grog)to the same non burned kaolinite. Different weight percentage ranged between (0,15,25,35and40)from grog and sawdust passed through mesh 50 to Deuchla-clay kaolinit.Cylindrical shape samples (30mm diameter and 30mm height) were prepared by the semi-dry methed,moulding pressure was 50 N/mm 2 . After drying at 110 o c,the samples were burnet in the furnace at temperatures 900,950,1000,1050,and 1100 o c. The sawdust burnt out and leaves air spaces which contribute to the high thermal insulation value. The fired samples were investigated to determine bulk density , porosity, compressive strength and the thermal conductivity .It was found that the increase of grog ratio produces a decrease in bulk density ,compressive strength and thermal conductivity, but addition of sawdust to the samples produces decrease greater than when addition the grog